Optimization of Nd-Doped LMA Fibers for High-Power Laser Emission Near 915 nm - Raphael Florentin; Kilian Le Corre; Thierry Robin; Alexandre Barnini; Roopa Prakash; Giorgio Santarelli; Herve Gilles; Sylvain Girard; Mathieu Laroche (IEEE Photonics Journal)
We report on the development of low numerical aperture (NA) Nd-doped large mode area (LMA) fibers with optimized core/clad geometry to achieve high-power laser emission near 915 nm while maintaining near diffraction-limited output beam. The influence of clad-to-core ratio on the detrimental amplified spontaneous emission (ASE) at 1050 nm and on the beam quality was studied experimentally in different amplifier configurations. We also show that bending the Nd-doped LMA fiber to a precise radius of curvature significantly improves the overall laser performances of these fibers by limiting both higher-order modes and spurious ASE at 1050 nm. The possibility of all-fiber multi-stages amplifier configurations with diffraction-limited output beam is finally discussed.